2007
DOI: 10.1002/anie.200701081
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Tetrafluorobutatriene by Complex Formation

Abstract: Now tamed: For decades preparative research on 1,1,4,4‐tetrafluorobutatriene was not pursued because of the explosive nature of the compound. Two new transition‐metal complexes containing a tetrafluorobutatriene ligand (see picture; green F/Cl, gray C, red O, purple P, orange Ir/Rh) have been prepared from the free triene, and both complexes are air‐stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Similarly we have shown that reduction of the perfluoro-sec-butyl ligand affords an inner-sphere construction of the perfluorobutatriene ligand in 51 [107]. In this case our inner-sphere construction of the ligand preceded a report of coordination of the free perfluorobutatriene [108].…”
Section: [ ( S C H E M E _ 4 ) T D $ F I G ]mentioning
confidence: 64%
“…Similarly we have shown that reduction of the perfluoro-sec-butyl ligand affords an inner-sphere construction of the perfluorobutatriene ligand in 51 [107]. In this case our inner-sphere construction of the ligand preceded a report of coordination of the free perfluorobutatriene [108].…”
Section: [ ( S C H E M E _ 4 ) T D $ F I G ]mentioning
confidence: 64%
“…In addition, it demonstrates that reductive inner-sphere construction of unsaturated fluorocarbon ligands like tetrafluoroallene and the previously reported example of tetrafluorobutatriene [19] represent useful alternative methods for their synthesis as opposed to the direct ligand substitution required when starting with the free fluorocarbon, [18,20,21] which itself can be difficult to prepare and handle. Further experimental and computational studies of the structures and reactivity of this new class of carbene complexes will be reported in due course.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless it was possible to synthesize two of its transition metal complexes directly from the triene, [M(η 2 -C 4 F 4 )(CO)(PPh 3 ) 2 Cl] (M = Ir, Rh). 74 Another tetrafluorobutatriene complex, Ir(η 5 -C 5 Me 5 )(PMe 3 )(η 2 -C 4 F 4 ), is known but was synthesized by reduction of a sec.-perfluorobutyl ligand within the coordination sphere of the metal. 75 Theoretical and practical studies on partially fluorinated butatrienes or higher cumulenes are rare.…”
Section: The Capability Of Cumulenes For Different Binding Modes To Mmentioning
confidence: 99%